Colour Doppler evaluation of varicose veins - Uddesh, Santosh Kumar; Singh, Krishna Kumar; Meshram, Sunita (International Journal of Research in Medical Sciences, 2016)
Background: Varicose veins are irreversibly dilated epifascial and perforating veins resulting from degenerative vascular wall changes, Depending on the aetiology, they are classified into Primary & Secondary forms. In the present clinical prospective studies, we evaluated the impact of ultrasound examinations on the pre-operative diagnosis of varicose veins and feasibility & efficacy of ultrasound. Methods: The current prospective study was conducted in the department of general surgery, Pt. J.N.M. College and associated Dr. BRAM Hospital Raipur, during a period form 1st august 2006 to 15th Nov 2007. Detail history was taken from patient as appropriate. A thorough clinical examination was done. The patients were then subjected to the series of investigations. The routine investigations were performed. Then all the patients were submitted for colour Doppler study. Other clinical diagnostic tests were also done. Other relevant examinations were also performed. The patients were then submitted for colour Doppler examination of lower limb with the help of Department of radiology. The groin and both lower limb scanned for seeking the common femoral, superficial femoral, popliteal, short saphenous, peroneal, anterior and posterior tibial veins. Any reflux at saphenous-femoral junction, dilatation and tortuousity as veining, reversal of flow, to locate the incompetent perforators. Results: The study included patients from 10-70 years of age group. The incidence was maximum (48%) in 31-50 yrs of age group. Sex wise distribution was nearly M: F- 5.25: 1. In our study, male appear to be more prone for the development of varicosity (84%). In our study it was found that maximum incidence noted in low socioeconomic status was 56%, second most common incidence noted in middle socioeconomic status (40%). Out of 25 patients one patient had associated thrombosis. In our study varicose vein was associated with anaemia 32%. Out of 25 patients, two patients received surgical management and 23 were managed conservatively. Conclusions: Duplex ultrasound scanning is non-invasive, early, safe and sensitive investigation of choice.